2019
DOI: 10.1051/bioconf/20191502005
|View full text |Cite
|
Sign up to set email alerts
|

Austrian Pinot blanc wines: Typicity, wine styles and the influence of different oenological decisions on the volatile profile of wines

Abstract: Pinot blanc is found in all wine regions of Austria. However, it plays an economically subordinate role compared to the most important white grape variety, Grüner Veltliner. The concept of wine typicity and terroir is that the geographical origin and oenological practices, along with the grape variety, make an important contribution to the final expression of the finished wine. The purpose of this study was to discuss different styles of Austrian Pinot blanc wines and to discuss the various wine production dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Despite its widespread national and international production, only a few recent studies on the volatile and sensory profiles of Pinot Blanc wines are available in the literature. The aroma of Austrian Pinot Blanc wines was studied to characterize their typical sensory traits [11]. The authors associated the "pear"aroma to the particular typicity of Austrian Pinot Blanc wines; this aroma was associated with short-and long-chain esters, such as ethyl (E, Z)-2,4-decadienoate and methyl (E)-geranoate [12].…”
Section: Introductionmentioning
confidence: 99%
“…Despite its widespread national and international production, only a few recent studies on the volatile and sensory profiles of Pinot Blanc wines are available in the literature. The aroma of Austrian Pinot Blanc wines was studied to characterize their typical sensory traits [11]. The authors associated the "pear"aroma to the particular typicity of Austrian Pinot Blanc wines; this aroma was associated with short-and long-chain esters, such as ethyl (E, Z)-2,4-decadienoate and methyl (E)-geranoate [12].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies used alternative names to typicality such as exemplarity [25], representativity [26], or typicity [27]. The reliability of typicality measurements depends on the expertise or familiarity of the tasters with regard to the category at hand as well as on the between-judges agreement [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of monoterpenes for the typicity of German Pinot blanc was emphasised by [56]. Higher concentrations of free monoterpenes were associated with the fresh fruity wine type (lemon, green apple, and grapefruit) [58]. It could also be shown that atypical wines of the 2017 vintage had a higher value for the citrus fruit descriptor.…”
Section: Discussionmentioning
confidence: 99%
“…The determination of the quantitative main aroma compounds, such as relevant higher alcohols, relevant short and medium-chain carboxylic acids, some carbonyl compounds and ester compounds, was carried out using a partial SIDA-HS-SPME-GC-MS method [58].…”
Section: Quantification Of Main Flavouring Substancesmentioning
confidence: 99%